Region, netværk og materiel kultur - Linaa, Jette (Hikuin, 2008)
Region, network and material culture By Jette Linaa Plotting phenomena onto maps is a basic archaeological craft. Numerous works by distinguished scholars have given us hundreds of maps where areas with similar phenomena such as brooches, grave equipment, pots etc. have been pronounced to be regions. But what constitutes a region? How do we define regions, sub-regions, local groups etc? Are the archaeological regions of today of any relevance to past society? Or are they an analytical tool? Our insight into the archaeological record, the ruins of past societies, is increasing rapidly. We are faced with traces of a massive diversity, where no single or simple explanation, geographical or otherwise, seems to be sufficient. So should we use the region today, or should we abandon it? This article offers a few preliminary thoughts on the nature and relevance of regions based on observations in medieval north Zealand.